Prevalence and Determinants of Disordered Eating Behaviours and Feeding and Eating Disorders among Schooling Adolescents in Ibadan, Nigeria (African Journal of Biomedical Research, 2023)
Feeding and Eating disorders (FEDs) are the third commonest chronic condition in adolescents, after obesity and asthma, and are often preceded by disordered eating behaviours (DEBs) which are abnormal eating patterns that predispose to FEDs. They constitute public health importance as a result of significant association with decreased quality of life, and substantial medical and psychiatric complications among adolescents. The prevalence of DEBs and FEDs has been on the increase in the western world following the onset of the pandemic with varying reports in developing countries. Therefore, this study was carried out to determine the prevalence of DEBs and FEDs, the associated sociodemographic correlates, determinants and their relationship with nutritional status. In a descriptive cross-sectional study design, 411 schooling adolescents aged 13 to 19 years were selected using a multistage random sampling technique and a pre-tested self-administered questionnaire was used to collect data on socio-demographic characteristics and other determinants. The SCOFF screening tool and DSM V diagnostic tool were used to identify those with DEBs and FEDs respectively. Participants’ weight and height were measured, their nutritional status classified using the WHO z-score. All data were analyzed using the IBM Statistical Package for Social Science version 20.0. The participants comprised 180 males (43.79%) and 231 females (56.21%) with a male to female ratio of 1:1.28. Our data showed that more than one (28.22%) out of every four participants has DEBs, and more than half (61.4%) of all the participants have one sub-type of FEDs or the other. The presence of chronic illness (OR=4.43), the effect of peer pressure on eating habits (OR=2.16), parental concern about body image (OR=2.12) and recent major life events (1.79) were independently associated with both DEB and FEDs, and there is a statistically significant association between FEDs and nutritional status but not with DEBs. We concluded that DEBs and FEDs are common among schooling adolescents in IBNLGA. Thus, there is a need for increased public awareness and deliberate efforts at prevention and early identification through routine screening in secondary schools. Special attention must also be given to the eating habits of adolescents with chronic illnesses